2022
DOI: 10.1038/s41467-021-27944-8
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1 Interacts with TRIM28 and DNA-PK to release paused RNA polymerase II and activate target gene transcription in response to hypoxia

Abstract: Hypoxia-inducible factor-1 (HIF-1) is a transcription factor that acts as a regulator of oxygen (O2) homeostasis in metazoan species by binding to hypoxia response elements (HREs) and activating the transcription of hundreds of genes in response to reduced O2 availability. RNA polymerase II (Pol II) initiates transcription of many HIF target genes under non-hypoxic conditions but pauses after approximately 30–60 nucleotides and requires HIF-1 binding for release. Here we report that in hypoxic breast cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 80 publications
0
37
0
Order By: Relevance
“…They also showed a role for DNA-PK in the release of paused Pol II and transcriptional activation-coupled DDR signaling on these genes, altogether suggesting transcriptional elongation requires DNA break-induced signaling involving the functional interplay between KAP1 and DNA-PK (Bunch et al, 2015). In line with these studies, another group recently showed that DNA-PK phosphorylates KAP1 at Ser824 to activate transcription of hypoxia-inducible genes by recruiting CDK9 to hypoxia response elements in a HIF1dependent manner (Yang et al, 2022)…”
Section: Kap1 Site-specific Phosphorylation and A Possible Activating...mentioning
confidence: 71%
“…They also showed a role for DNA-PK in the release of paused Pol II and transcriptional activation-coupled DDR signaling on these genes, altogether suggesting transcriptional elongation requires DNA break-induced signaling involving the functional interplay between KAP1 and DNA-PK (Bunch et al, 2015). In line with these studies, another group recently showed that DNA-PK phosphorylates KAP1 at Ser824 to activate transcription of hypoxia-inducible genes by recruiting CDK9 to hypoxia response elements in a HIF1dependent manner (Yang et al, 2022)…”
Section: Kap1 Site-specific Phosphorylation and A Possible Activating...mentioning
confidence: 71%
“…Recently published RNA sequencing data from our laboratory revealed that NARF mRNA expression was significantly induced by hypoxia in SUM159 human breast cancer cells ( 26 ). To investigate whether NARF expression is correlated with a HIF signature in breast cancers, we analyzed mRNA expression data from 1218 breast cancer specimens in The Cancer Genome Atlas (TCGA) breast cancer database using Pearson’s correlation ( R ) test.…”
Section: Resultsmentioning
confidence: 99%
“…RT-qPCR assays were performed as described previously ( 26 ). Briefly, total RNA was isolated using TRIzol (Invitrogen) and reverse-transcribed using the High-Capacity RNA-to-cDNA Kit (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, it is not clear whether DNA break and DDR are byproducts of transcriptional activation or play an active role in it. However, it should be noted that inhibiting DDR or critical DNA repair enzymes interferes with Pol II pause release and gene expression [4][5][6]17,24,89 , suggesting a proactive role of DNA break and DDR in transcriptional activation. Moreover, it is not difficult to find the examples of purposed and functional DNA fragmentation and small nucleic acid production in DNA metabolisms such as DNA replication 90 , recombination 91 , and repair 92 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, stress-inducible genes respond to environmental signals and cellular needs, and their synchronized and rapid gene expression is crucial for cell survival, maintenance, and growth 2,5,[8][9][10] . Representative examples are serum/growth factorinducible immediate early genes (IEGs) 2,5 , heat shock genes [11][12][13] , neurotransmitter-inducible genes 4,14 , enhancer RNA genes 15,16 , and hypoxia-inducible genes 17,18 .…”
Section: Introductionmentioning
confidence: 99%